A new species of the genus Catillopecten (Bivalvia: Pectinoidea: Propeamussiidae): morphology, mitochondrial genome, and phylogenetic relationship - Lin, Yi-Tao; Li, Yi-Xuan; Sun, Yanan; Tao, Jun; Qiu, Jian-Wen (Frontiers in Marine Science, 2023)
We describe Catillopecten margaritatus n. sp. (Pectinoidea: Propeamussiidae) based on samples collected from the Haima cold seep in the South China Sea. It is the first species of Catillopecten reported from a cold seep, and the second species of the genus reported from chemosynthetic habitats. Morphologically, the new species can be distinguished from all congeneric species by its large maximum shell size, relatively small auricle length, smooth shell surface without monocrystal aerials, the presence of longitudinal radial ridges on the left valve, and the alternated rounded striae and distal and proximal growth lines of prisms on the right valve. Anatomically, this new species can be distinguished from C. vulcani Schein-Fatton, 1985 by its anteriorly located auriculate gills, compared to the centrally located lamellar gills of the latter, and the different locations of the pericardium. Sequence comparison and phylogenetic analysis based on the 18S rRNA fragments supported the placement of the new species in Catillopecten. We also report the mitogenome of C. margaritatus n. sp. as the only reported mitogenome of the family Propeamussiidae, which differs from those of other scallops substantially in gene order arrangement. Divergence time estimation revealed that Propeamussiidae and Pectinidae diverged in the early Carboniferous, while Catillopecten and Parvamussium Sacco, 1897 diverged during the late Cretaceous to early Eocene. Finally, we presented a key to the species of Catillopecten.